Preparation of multilayer periodic nanopatterned WO3-based photoanode by reverse nanoimprinting for water splitting. (6th July 2021) - Kim, Jungmin; Lee, Hoyoung; Choi, Jun-Hyuk; Park, Chan; Lee, Byeongjun; Jung, Joo-Yun; Park, Jong Hyeok; Lee, Jihye; Cho, Seong J
Abstract: Photoelectrochemical (PEC) water splitting has been studied extensively as an environmentally friendly technology for hydrogen production using solar energy. WO3 is considered a promising semiconducting material for photoanodes due to its high electron mobility, good hole diffusion length, and chemical stability. Periodic nanostructures of WO3 have been investigated for enhancing the PEC performance of WO3 -based photoanodes. In this study, facile fabrication of periodic nanostructures of WO3 was achieved using reverse nanoimprint lithography, and the multilayer stacking of nanopatterned WO3 film was also confirmed. The multilayer nanopatterned WO3 films were used as photoanodes for PEC water splitting. The performance of the fabricated photoanode in PEC was 2 times higher than that of planar WO3 film due to its higher light absorbance and lower charge transfer resistance.